Chronic diseases in the context of fundamental biology - Kordium, V.A. (Вiopolymers and Cell, 2017)
The problem of chronic diseases is analyzed from the perspective of general biology. We develop and substantiate the idea that the chronic diseases are an evolutionary mechanism of cleansing the population and the species of its mutational load. This is achieved by keeping self-restoration systems of a chronically damaged organism in the off-state, unlike in the ‘permissible’ self-restoration triggered by the acute damage. Evolutionary, chronic diseases serve as a somatic marker for the accelerated elimination of their carriers.